2021
DOI: 10.1139/cgj-2020-0254
|View full text |Cite
|
Sign up to set email alerts
|

Shear modulus and hysteretic damping of sensitive eastern Canada clays

Abstract: The shear modulus and equivalent viscous damping ratio of three sensitive clays from the sediments of the Champlain Sea were investigated using a combined triaxial simple shear apparatus. The tests were conducted on undisturbed samples and were carried out on a wide range of shear strain from about 0.001% to 1%. The values of the small strain shear modulus of the tested clays were further confirmed through a series of piezoelectric ring actuator and MASW tests. Although the shear modulus and damping ratio of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…Matasovićand Vucetic (1995) summarized the published data and found that the g tp of Cariaco undisturbed marine clays was 0.1%. Abdellaziz et al (2020) investigated the g tp of three types of Eastern Canada clays and concluded that the g tp for the clays with I p =36 and 38 ~40 was 0.2%, while it was 0.3% for the clays with I p =28. It was noted that the variation pattern of g tp in Abdellaziz et al (2020) is contrary to previous studies but was not explained in detail.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Matasovićand Vucetic (1995) summarized the published data and found that the g tp of Cariaco undisturbed marine clays was 0.1%. Abdellaziz et al (2020) investigated the g tp of three types of Eastern Canada clays and concluded that the g tp for the clays with I p =36 and 38 ~40 was 0.2%, while it was 0.3% for the clays with I p =28. It was noted that the variation pattern of g tp in Abdellaziz et al (2020) is contrary to previous studies but was not explained in detail.…”
mentioning
confidence: 99%
“…Abdellaziz et al (2020) investigated the g tp of three types of Eastern Canada clays and concluded that the g tp for the clays with I p =36 and 38 ~40 was 0.2%, while it was 0.3% for the clays with I p =28. It was noted that the variation pattern of g tp in Abdellaziz et al (2020) is contrary to previous studies but was not explained in detail. Likitlersuang et al (2014) observed that the g td of Bangkok clays ranged from 0.03% to 0.07%, which was defined as the shear strain at G/G max = 0.7 within the normalized shear modulus versus shear strain curves.…”
mentioning
confidence: 99%